The Influence of Work Posture and Work Environment on Sick Building Syndrome in Port Service Company Employees - Kinanti, Juwitaning Sekar; Kurniasih, Dewi; Rachmat, Aulia Nadia (Jurnal Teknologi, 2024)
Sick Building Syndrome is a combination of health problems that a human feels only when doing activities inside a building. This situation is due to various factors, such as ergonomic factors and a work environment that is not in accordance with applicable regulations. The office building of the Port Service Company has poor building conditions, such as a poor ventilation system, some work facilities that are not ergonomic, and the physical environment of lighting and work climate that is not up to standard. This study was conducted to determine the general description of the incidence of SBS in the office building of the Port Services Company and to determine the effect of work posture and work environment on SBS complaints. The statistical method used in this study is binary logistic regression test. The results of statistical testing showed that work posture (p-value=0.018) and lighting (p-value=0.027) had an effect on sick building syndrome.